Physical characteristics, band-gap and glass-transition temperature estimations of (CdTe)100−x(SbSe)x glasses. (21st October 2021) - Kebaili, Imen; Znaidia, S; Boukhris, Imed; Somaily, H H; Algarni, H; Hegazy, H H; Neffati, R; Dahshan, A
Abstract: Given the importance of (CdTe) and (SbSe) properties, one can presume exceptional applications of (CdTe)100−x (SbSe)x compounds. Therefore, diverse physicochemical characteristics were investigated. The overall number of coordination (CN), number of constraints (Nc ), heat of atomization (Ha ), cohesive energy (CE), and lone-pair electrons (LPE) of (CdTe)100−x (SbSe)x chalcogenide glasses were studied using the known chemical bond approach. CN and Nc diminished when the amount of SbSe was increased, whereas CE increased due to the decrease in Cd–Cd homo-polar bonds. The band gap (Eg ) was assessed and found to diminish with SbSe expansion. A good agreement was found between the Eg assessments and previous experimental studies. The conduction and valence band positions were also determined. The glass-transition temperature (Tg ) was assessed and found to diminish with SbSe expansion.